The Role of Population Activities as Extraculicular Required on Democratic Characters of Students - Esep Regan Pribadi; Dasim Budimansyah; Rahmat Rahmat (CV. Rayyan Dwi Bharata, 2002)
This research is motivated by the phenomenon of the decline of national morality, especially the younger generation, especially among students. This is indicated by the increasing prevalence of social-social phenomena such as the fading tradition, culture, social values, ethical norms and noble mind and character have begun to fade among students. The approach of this research is qualitative with a case study method. Data collection techniques in this study were observation, interviews, literacy studies, documentation studies and tringulation. The findings of this study are (1) the implementation of the scouting program activities designed and implemented effectively and efficiently as a means of strengthening the character values of students. (2) Strengthening the value of democratic character of students through scouting activities as compulsory extracurricular activities consisting of routine, spontaneous and exemplary activities. (3) Obstacles to be found include lack of active participation from students, lack of numbers of scout coaches and trainers, financial support, school skills in planning and implementing programs, and lack of facilities and infrastructure (4) The efforts made are the existence of technical guidance from the government, making planning and implementing programs that are interesting, effective, and efficient, requesting support from parents, using adequate facilities and infrastructure